What Caging Force Cells Feel in 3D Hydrogels: A Rheological Perspective. Issue 17 (21st July 2020) - Ciccone, Giuseppe; Dobre, Oana; Gibson, Graham M.; Rey, Jose Manuel; Gonzalez–Garcia, Cristina; Vassalli, Massimo; Salmeron–Sanchez, Manuel; Tassieri, Manlio
Abstract: It has been established that the mechanical properties of hydrogels control the fate of (stem) cells. However, despite its importance, a one‐to‐one correspondence between gels' stiffness and cell behavior is still missing from literature. In this work, the viscoelastic properties of poly(ethylene‐glycol) (PEG)‐based hydrogels are investigated by means of rheological measurements performed at different length scales. The outcomes of this work reveal that PEG‐based hydrogels show significant stiffening when subjected to a compressional deformation, implying that conventional bulk rheology measurements may overestimate the stiffness of hydrogels by up to an order of magnitude. It is hypothesized that this apparent stiffening is caused by an induced "tensional state" of the gel network, due to the application of a compressional normal force during sample loading. Moreover, it is shown that the actual stiffness of the hydrogels is instead accurately determined by means of both passive‐video‐particle‐tracking (PVPT) microrheology and nanoindentation measurements, which are inherently performed at the cell's length scale and in absence of any externally applied force in the case of PVPT. These results underpin a methodology for measuring hydrogels' linear viscoelastic properties that are representative of the mechanical constraints perceived by cells in 3D hydrogel cultures. Abstract : A multi–scale rheological approach reveals the true mechanical properties of poly(ethylene‐glycol) hydrogels, which are extensively used as 3D culture platforms for in vitro and in vivo applications. This study underpins the strategy for a quantitative evaluation of a one–to–one correlation between the linear viscoelastic properties of hydrogels and (stem) cell fate.